A standalone tunable vibration absorber with self-sensing magnetorheological elastomer. (29th September 2021) - Kwon, Haeun; Song, Yoonkyoung; Park, Jae-Eun; Kim, Young-Keun
Abstract: This study proposed a standalone module of a tunable vibration absorber (TVA) using a self-sensing magnetorheological elastomer (MRE) that replaced accelerometer sensors required for the automatic tuning of a TVA. The manufactured self-sensing MRE can estimate the frequency of the input vibration and change its stiffness to tune the absorber system. Unlike previous MRE-based TVAs, the proposed TVA module is free from external sensors and is designed as a compact system to be easily attached to the target application, such as a linear compressor. In this paper, a self-sensing MRE of 10 mm in thickness was manufactured for rigid support of the absorber mass, allowing the electrical resistance to change by 1, 375% from 20.6 to 283 kΩ owing to a compression strain of 2.5 mm. In addition, test results showed that the self-sensing MRE can estimate the vibration frequency within the error of 0.04 Hz. Under a magnetic field of 232 mT, the designed self-sensing MRE achieves a stiffness variation of approximately 125% for tuning the absorber frequency from 39 to 45 Hz. Thus, based on a series of experiments, the vibration sensing and control performance of the proposed self-sensing MRE TVA was validated.